Building and Streets / Spanish Town, St. Catherine, Jamaica - Georgian Society of Jamaica (St. Catherine, Jamaica : Georgian Society of Jamaica, 1970)
Two photographs showcasing the architectural design and styles of a variety of buildings in Jamaica's old capital, Spanish Town in the parish of St. Catherine. One of the images outlines the corner of Martin Street.
level 2
Available on the Special Collection Floor.
Keywords: Georgian Society of Jamaica; Spanish Town, St. Catherine, Jamaica; Photograph